Cell‐based tissue engineering augments tendon‐to‐bone healing in a rat supraspinatus model. Issue 3 (15th October 2012) - Loeffler, Bryan J.; Scannell, Brian P.; Peindl, Richard D.; Connor, Patrick; Davis, Daniel E.; Hoelscher, Gretchen L.; Norton, H. James; Hanley, Edward N.; Gruber, Helen E.
Abstract Rotator cuff pathology causes substantial pain/disability and health care costs. Cell‐based tissue engineering offers promise for improved outcomes in tendon to bone healing. Cells from the tendon‐bone interface were used here to amplify surgical defect healing in a rat model. Cells from tendon‐to‐bone interface of the rotator cuff were seeded in sponges and implanted into critical rotator cuff defects: Group I, control; II, surgical defect only; III, suture‐repaired defect; IV, surgical defect, repair with sponge only; V, surgical defect, repair with sponge with cells. Three, 6‐, and 12‐week results were assessed for histologic features. At 3 weeks, histologic indices in Group V were significantly increased versus other treatment groups. Group V (12 weeks) showed significantly improved collagen organization versus other treatment groups; there was no difference in collagen organization in Group I versus V. In summary, increased cellularity, inflammation, vascularity, and collagen organization were present at 3 weeks; increased collagen organization at 12 weeks in Group V provides evidence for improved healing with cells. Data further support the utility of tendon‐bone interface cells in rotator cuff healing. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 407–412, 2013